Quality of Life and Adherence to Imatinib Mesylate Therapy in Chronic Myeloid Leukemia Patients at Dharmais Cancer Hospital Jakarta - Nisha Virginia; Maksum Radji; Lucia Rizka Andalucia (Indonesian Journal of Cancer, 2021)
Background: Quality of life and adherence to long-term imatinib mesylate (IM) therapy is a major factor in achieving therapeutic effects in patients with chronic myeloid leukemia (CML). However, the data of the quality of life and adherence level is inconsistent in various studies and is also not fully understood yet in Indonesia. Methods: This is an observational study (single-centered) using a cross-sectional design. CML patients older than 18 years old with National Health Insurance (JKN) at the Dharmais Cancer Hospital (RSKD) Jakarta who used IM for at least one month were tested using the Medication Adherence Questionnaire (MAQ) and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30 (EORTC QLQ-C30) from March to April 2020.Result: A total of 50 CML patients were included in the study (male: female ratio = 1.08: 1), had a good median score of global health status/QoL, and had a good function and symptom scales, except for the fatigue symptom scale (median: 33.33; 25th percentile - 75th percentile: 11.11– 44.44). The patient adherence rate was dominated by adherent patients (20/50; 40.0%). Comparative analysis revealed that the scale of QoL (p = 0.028) and fatigue (p = 0.094) variables showed statistically significant differences between adherent and non-adherent subjects.Conclusions: This study showed that two-fifth of patients were considered to be non-adherent. Adherent patients were known to have higher QoL than non-adherent patients. Meanwhile, patients with severe symptoms of fatigue were found to be non-adherent to IM therapy.